Clinical and Pharmacological Importance of Micronutrients for Pregnant Women and Newborns - Rasulov Saydullo Kurbanovich; Rustamova Kh. Kh; Narmetova S. Ya (Researchparks Publishing, 2022)
The aim of the study was to study the micronutrient composition and the physiological role of the national product - grape gurob, in order to provide nutritional support, correction and prevention of macro- and microelement deficiencies in the